Quality Changes of Fish Sausage Incorporated with Potato Starch Powder at Room Temperature - Hegde, Ganapati; T.C., Chandrasekhar; K.C, Dora (Fishery Technology, 2025)
Fish sausages were prepared from the minced meat of croaker (Johnius spp.)by mixing with 7% potato starch dried powder. Control samples without potato starch dried powder were also prepared and both samples were stored at room temperature (28 i 2Â°C). The studies showed that the control samples remained in acceptable condition for 3 days, where as the potato starch powder added samples were in acceptable condition for 2 days only. The total plate count of control samples were lower than that of the potato starch added samples.